Exploring the extent of mental health practice: content and cluster analysis of techniques used in HIV testing and counselling sessions in Uganda. Issue 2 (1st February 2023) - Martin, Faith; Clowes, Eleanor; Nalukenge, Winifred; Clark, Cain; Lazarus, Oucul; Birungi, Josephine; Seeley, Janet
ABSTRACT: There is an urgent need for greater provision of mental health services to people living with HIV. HIV testing and counselling (HTC) sessions diagnose HIV and offer appropriate psychosocial support and behavioural messages to support people to link into HIV care. It is not known to what extent HTC currently addresses mental health. We examined transcriptions of 116 audio-recorded HTC sessions delivered in Uganda against a checklist of mental health techniques. Hierarchical cluster analysis explored co-occurrence of techniques. Core counselling skills were very commonly present, and co-occurred. Assessment techniques were not commonly seen. Specific therapy techniques to treat anxiety or depression were not present. HTC staff are a resource for delivering mental health care for people with HIV, owing to their strong fundamental counselling skills. However, training is needed in assessment and evidence-based therapies. Provision of fuller assessment and interventions may increase detection and signposting for mental health and alcohol use, both of which may affect linkage into care. HTC staff have fundamental skills that could also be developed to train and supervise other staff to provide much needed mental health support to people living with HIV. Future research should develop brief mental health interventions for delivery by HTC staff.